Barriers to telehealth access among homebound older adults - Kalicki, Alexander V.; Moody, Kate A.; Franzosa, Emily; Gliatto, Peter M.; Ornstein, Katherine A. (Journal of the American Geriatrics Society (JAGS), 2021)
Background/Objectives To identify major barriers to video‐based telehealth use among homebound older adults. Design Cross‐sectional survey. Setting A large home‐based primary care (HBPC) program in New York City (NYC) serving 873 homebound patients living in the community. Participants Sixteen primary care physicians. Measurements An 11‐item assessment of provider perceptions of patients' experience with and barriers to telehealth. Results According to physicians in the HBPC program, more than one‐third (35%) of homebound patients (mean age of 82.7; 46.6% with dementia; mean of 4 comorbidities/patient) engaged in first‐time video‐based telehealth encounters between April and June 2020 during the first COVID‐19 surge in NYC. The majority (82%) required assistance from a family member and/or paid caregiver to complete the visit. Among patients who had not used telehealth, providers deemed 27% (n = 153) “unable to interact over video” for reasons including cognitive or sensory impairment and 14% lacked access to a caregiver to assist them with technology. Physicians were not knowledgeable of their patients' internet connectivity, ability to pay for cellular plans, or video‐capable device access. Conclusion The COVID‐19 pandemic resulted in a large and dramatic shift to video‐based telehealth use in home‐based primary care. However, 4 months into the pandemic a majority of patients had not participated in a video‐based telehealth encounter due to a number of barriers. Patients lacking caregiver support to assist with technology may benefit from novel approaches such as the deployment of community health workers to assist with device setup. Physicians may not be able to identify potentially modifiable barriers to telehealth use among their patients, highlighting the need for better systematic data collection before targeted interventions to increase video‐based telehealth use.